Enhancing Students’ Narrative Writing Skills Through Peer Dynamic Assessment: A Classroom Action Research - Sarwanti, Sri; Sotlikova, Rimajon; Winarsih , Dwi (JOLLT Journal of Languages and Language Teaching, 2026)
This classroom action research aimed to improve students’ narrative writing skills through the implementation of Peer Dynamic Assessment (PDA). The study was conducted in three cycles involving 30 students of the eleventh grade. The data were collected through writing tests, observations, and interviews. The results showed continuous improvement in students’ writing performance. The mean scores increased from 66.5 in the pre-cycle to 73.2 in Cycle I, 78.6 in Cycle II, and 84.8 in Cycle III. The percentage of students achieving the minimum mastery criterion (KKM 75) also rose from 26.7% to 93.3%. Students demonstrated better control of text structure, grammar, vocabulary, and mechanics. Qualitative findings revealed that students were more motivated and aware of their errors through collaborative feedback. These findings indicate that Peer Dynamic Assessment is an effective approach to enhance both cognitive and affective aspects of writing instruction.